Alpha 2-adrenoceptor agonists stimulate growth hormone secretion but have no acute effects on plasma cortisol under basal conditions. - Grossman, A; Weerasuriya, K; Al-Damluji, S; Turner, P; Besser, G (1987)
Ten normal male subjects were administered clonidine (0.1 and 0.2 mg) or a highly-selective alpha 2-adrenoceptor agonist S 3341 (1 and 2 mg) on separate occasions in a double-blind randomised placebo-controlled study; blood samples were obtained for measurement of serum GH and plasma cortisol via an indwelling venous cannula for 4 h after each drug administration. Both clonidine and S 3341 were equally effective at lowering supine, and particularly standing BP; both also caused mild sedation, although this was slightly less marked for S 3341. High doses of both clonidine and S 3341 significantly increased serum GH (peak increment after clonidine: 18.8 +/- 5.5 mU/l (mean +/- SEM); peak increment after S 3341: 21.1 +/- 4.8 mU/l). Neither drug affected plasma cortisol. It is concluded that GH release may be stimulated by alpha 2-adrenoceptor agonism. As S 3341 has slightly less central activity than clonidine at the doses employed, but is at least equally potent at stimulating GH release, it is probable that the alpha 2-adrenoceptor stimulation of GH release occurs outside the blood-brain barrier. The pituitary-adrenal axis appears resistant to manipulation of alpha 2-adrenoceptors under basal conditions.